PDMS-Based Nanoimprint Lithography for Photonics - Pudis, Dusan; Jandura, Daniel; Gaso, Peter; Suslik, Lubos; Hronec, Pavol; Martincek, Ivan; Kovac, Jaroslav; Berezina, Sofia (Communications - Scientific Letters of the University of Zilina, 2014)
Implementation of planar surface photonic crystal (PhC) structures leads to improvement of optical properties of optoelectronic devices. Application of such structures can be attractive for overall and local enhancement of light from patterned areas of the light emitting diode surface and for lightwave-guiding devices. We present techniques useful for PhC patterning and for patterning of different optic structures in surface of new promising material polydimethylsiloxane (PDMS). Paper proposes nanoimprint technology for fabrication of PhC in the surface of thin PDMS membranes for possible application in light emitting diodes. By PDMS patterning and its positioning on the device surface one can achieve original optical properties of optoelectronic devices. We also present new technique for fabrication of surface-relief fiber Bragg grating (SR FBG) based on PDMS waveguide.
Keywords: polydimethysiloxane; nanoimprint lithography; photonic crystal